2019
DOI: 10.5194/nhess-2019-270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Summer variation of the UTCI index and Heat Waves in Serbia

Abstract: Abstract. The objective of this paper is the assessment of bioclimatic conditions in Sebia. A special emphasis has been given to the heat budget bioclimatic Universal Thermal Climate Index (UTCI) whose purpose is to evaluate degree of thermal stress that human body is exposed to during the last twenty years. In addition, the thresholds of daily maximum temperatures are analysed in order to identify increase and frequency of heat waves in Serbia. For this research, daily and hourly (07 h and 14 h) meteorologica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Even though heatwaves in 2003 and 2010 draw much attention to Western Europe and Russia, it is noteworthy to mention the particularly intensive heatwave of 2007 in South-East Europe. Pecelj et al [70] noted that UTCI values at 14 h were as high as 48.4 • C in Novi Sad (Northern Serbia). The authors stated that due to the changes in air temperatures and the frequency of occurrence of extreme heatwave events, it can be expected that such high values of UTCI are likely to occur in the future.…”
Section: Southern and Southeastern Europementioning
confidence: 99%
See 1 more Smart Citation
“…Even though heatwaves in 2003 and 2010 draw much attention to Western Europe and Russia, it is noteworthy to mention the particularly intensive heatwave of 2007 in South-East Europe. Pecelj et al [70] noted that UTCI values at 14 h were as high as 48.4 • C in Novi Sad (Northern Serbia). The authors stated that due to the changes in air temperatures and the frequency of occurrence of extreme heatwave events, it can be expected that such high values of UTCI are likely to occur in the future.…”
Section: Southern and Southeastern Europementioning
confidence: 99%
“…A major part of Poland's territory was affected by conditions very strenuous for the organism with UTCI values higher than 40 • C after 1990. Similar changes in extreme values of UTCI were observed in regional studies in Poland [75], but also in other European countries-e.g., Hungary [76] or Romania [77], Serbia [70].…”
Section: Central and Western Europementioning
confidence: 99%
“…Serbian researchers (Pecelj et al, 2019) have also found, among other things, that in addition to the increase in the frequency of heat waves, a growth trend is also detected in their duration.…”
Section: Introductionmentioning
confidence: 93%
“…Heat waves also have a very detrimental effect on the development of plants, for example, maize does not tolerate heat stress above 35 °C, its development slows down or even stops (Somfalvi-Tóth, 2018). It is worth looking at the yield of maize for the period 2010-2019(KSH, 2019. Weaker yields in 2012, 2015, 2017 may correlate with the number of 31, 32, 33 heat wave days occurring in these years.…”
Section: Introductionmentioning
confidence: 99%
“…Napoli et al have assessed the thermal bioclimate of Europe for the summer season and concluded that an increase in heat stress up to 1 • C was observed from 1979 to 2016 [27]. Some scholars pointed out that southern Europe (Crete Island in Greece, Eastern Mediterranean, Athens, Madrid (Spain), Novi Sad (Vojvodina, Northern Serbia)) were under high temperature and pressure, and climate warming has led to a significant increase in the frequency and duration of high-temperature heat waves in southern Europe and a decline in climate comfort [28][29][30][31][32][33][34][35]. In central Europe, climate change has led to an increase in the number of strong and very strong heat stress days in Poland [36].…”
Section: Introductionmentioning
confidence: 99%